Discourse Analysis Yomiuri Editorial Online Newspaper (An Positive Empirical View) - Hety Nurohmah (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Discourse is the highest grammatical units bound together by ideas, ideas and backgrounds disclosure as a context into a single unit or a unified whole. This study aims to describe the discourse of the online news text narrative of the Japanese mass media, namely Yomiuri online, from a positive empirical point of view. Discourse analysis based on this positive empirical view discusses how discourse is correct syntactically and semantically, in other words how the discourse relates between sentences in a text which makes a discourse intact in form (cohesion) and meaning (coherent). By using a qualitative descriptive research method, the results of this study are the most prominent discourse markers listed in the online news discourse of Yomiuri Online, namely the comparative markers which are also the markers of the integrity of the discourse.